The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/tox.23408
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect and molecular mechanism of Salvia Miltiorrhiza on rats with acute brain injury after carbon monoxide poisoning based on the strategy of internet pharmacology

Abstract: The pathogenesis of brain injury caused by carbon monoxide poisoning (COP) is very complex, and there is no exact and reliable treatment in clinic. In the present study, we screened the therapeutic target and related signal pathway of Salvia Miltiorrhiza for acute COP brain injury, and clarified the pharmacological mechanism of multicomponent, multitarget, and multisignal pathway in Salvia Miltiorrhiza by network pharmacology. To further verify the therapeutic effect of Salvia Miltiorrhiza on acute brain injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In the aftermath of a stroke, IL-17 is critical in boosting the inflammatory response and causing secondary brain damage ( 42 ). Studies have demonstrated that the MAPK/ERK signaling pathway could enhance microcirculation, encourage angiogenesis, prevent cell apoptosis, and shield the brain tissue from toxicity effect of carbon monoxide ( 43 ). The FoxO signaling pathway plays an important role in cell proliferation, apoptosis, differentiation, and resistance to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the aftermath of a stroke, IL-17 is critical in boosting the inflammatory response and causing secondary brain damage ( 42 ). Studies have demonstrated that the MAPK/ERK signaling pathway could enhance microcirculation, encourage angiogenesis, prevent cell apoptosis, and shield the brain tissue from toxicity effect of carbon monoxide ( 43 ). The FoxO signaling pathway plays an important role in cell proliferation, apoptosis, differentiation, and resistance to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…ACOP can make patients with systemic hypoxia, abnormal synthesis of adenosinetriphosphate (ATP), resulting in multiple organ function damage, 1,2 among which, the most direct and serious consequences are in the central nervous system and cardiovascular system. 3 At present, the pathogenesis of brain injury caused by ACOP is not clear, and there is no reliable detoxification therapy. Hyperbaric oxygen therapy is the main treatment strategy in clinical practice, however, it can cause many serious complications, especially in severe patients and experimental animal models, such as non-convulsive status epilepticus, pulmonary edema, cerebral edema, and cerebral hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Acute carbon monoxide poisoning (ACOP) is one of the important causes of poisoning death that endanger human life safety. ACOP can make patients with systemic hypoxia, abnormal synthesis of adenosine–triphosphate (ATP), resulting in multiple organ function damage, 1,2 among which, the most direct and serious consequences are in the central nervous system and cardiovascular system 3 . At present, the pathogenesis of brain injury caused by ACOP is not clear, and there is no reliable detoxification therapy.…”
Section: Introductionmentioning
confidence: 99%